A HISTORY OF DIGITAL MARKETING - Kurolov Maksud Obitovich (Scholar Express Journals, 2022)
The current paper delves into historical properties of Digital Marketing and Marketing Strategy. The study of Digital marketing is essential especially for companies who intend to increase their outcome by applying the historical approaches to their management strategy. The paper is intended to help organizations to improve their effectiveness by promoting internally amid their members, the development of the capacity to generate innovative ideas.
Keywords: Marketing; strategy; digital marketing,marketing